2021
DOI: 10.1007/s00572-020-01015-0
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal fungal community structure in a young orchard of grafted and ungrafted hybrid chestnut saplings

Abstract: Ectomycorrhizal (ECM) fungal community of the European chestnut has been poorly investigated, and mostly by sporocarp sampling. We proposed the study of the ECM fungal community of 2-year-old chestnut hybrids Castanea × coudercii (Castanea sativa × Castanea crenata) using molecular approaches. By using the chestnut hybrid clones 111 and 125, we assessed the impact of grafting on ECM colonization rate, species diversity, and fungal community composition. The clone type did not have an impact on the studied vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Studies have shown that C. geophilum isolated from different geographical locations and hosts maintains a high degree of genetic diversity [ 40 , 41 , 42 ]. The inoculation of C. geophilum promoted the growth of host plant roots, improved the absorption and utilization of mineral elements, and regulated the secretion of secondary metabolites of the host plants, thereby enhancing the ability of plants to resist abiotic and biotic stress [ 43 , 44 , 45 ]. Numerous studies have shown that C. geophilum was able to improve the survival of host plants by increasing the biomass, photosynthesis, and mineral nutrient absorption, and weakened the transfer of Cd, lead (Pb), Cu, and zinc (Zn) from soil to plant roots [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that C. geophilum isolated from different geographical locations and hosts maintains a high degree of genetic diversity [ 40 , 41 , 42 ]. The inoculation of C. geophilum promoted the growth of host plant roots, improved the absorption and utilization of mineral elements, and regulated the secretion of secondary metabolites of the host plants, thereby enhancing the ability of plants to resist abiotic and biotic stress [ 43 , 44 , 45 ]. Numerous studies have shown that C. geophilum was able to improve the survival of host plants by increasing the biomass, photosynthesis, and mineral nutrient absorption, and weakened the transfer of Cd, lead (Pb), Cu, and zinc (Zn) from soil to plant roots [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%